Manejo na entressafra do arroz com herbicidas pré-emergentes para controle de arroz-daninho e redução do banco de sementes - Lucas, Tilio Adan (2023)
Weedy rice (Oryza sativa L.) is the most important weed in irrigated rice crop, being one of the main factors limiting cereal productivity in Rio Grande do Sul (RS), Brazil. One of the main management methods for this weed is the Clearfield® cultivation system, which allows for both pre- and post-emergence management of the crop, due to the tolerance of cultivars to herbicides from the imidazolinone chemical group. However, there are currently weedy rice biotypes resistant to these herbicides, necessitating the adoption of other management practices to adhere to the principles of integrated weed management. An alternative is autumnal management using pre-emergent herbicides to reduce the seed bank in the soil. However, as it is of the same species as cultivated rice, it is important to evaluate the impacts of using these herbicides on crop development. Thus, the objective of this study was to determine the effect of pre-emergent herbicide use in autumnal management on the control and reduction of the weedy rice seed bank. Field experiments were conducted in a randomized complete block design with four replications in a commercial rice production area during the 2021/22 and 2022/23 growing seasons in Dom Pedrito, RS, Brazil. The scheme used was factorial, with factor A consisting of different herbicide application times, referred to as June, July, and August, corresponding to 100, 78, and 47 days, and 42, 26, and 10 days before rice sowing for the agricultural years 2021/22 and 2022/23, respectively. Factor B consisted of the herbicides s-metolachlor (1440 g a.i. ha-1 ), sulfentrazone + diuron (210 and 420 g a.i. ha-1 ), piroxasulfone (170 g a.i. ha-1 ), and flumioxazin (50 g a.i. ha-1 ), in addition to the control (no application). The evaluated variables were control (%), number of plants (m2 ) at crop pre-harvest, number of full, viable, and non-viable wild rice seeds m-2 in the soil, as well as crop injury (%) and grain yield (kg ha-1 ). The herbicides showed control values below 25%, and low reduction of the seed bank in the soil, being considered ineffective in this application modality. The herbicides s-metolachlor, sulfentrazone + diuron, and flumioxazin exhibited the highest injury values; however, they did not significantly affect crop productivity. Thus, when applied before rice sowing, the herbicides s-metolachlor, sulfentrazone + diuron, pyroxasulfone, and flumioxazin do not provide satisfactory control and do not significantly reduce the wild rice seed bank.